Women and Manual Trades, 1975 (London, 1975)
1975 1974-79 "Women and Manual Trades, 1975" [BW0136], 1975, Trades Union Congress The Women and Manual Trades campaign and support network was set up in 1975 by women who were training or working in the building or other male-dominated trades.